Studi Pengaruh Berbagai Metode Treatment Pada Karakteristik Tepung Rumput Laut Sargassum Sp. - Maulida Wahyuni Putri (Prosiding, 2025)
This research aims to determine the effect of the Sargassum sp soaking method. using fresh water, salt water and distilled water to determine the characteristics of the flour produced. The analysis results showed that the highest flour yield was obtained by soaking using distilled water at 4.6%, followed by salt water at 4%, and fresh water at 3.73%. The highest protein content of flour was found in fresh water treatment at 30.6%, while the highest fat content was found in flour soaked in salt water reaching 20.59%, much higher than fresh water (5.03%) and distilled water (10.57%). The highest ash content was also observed in the saltwater treatment (32.57%). Soaking in fresh water produces the highest crude fiber content, namely 17.16%, followed by salt water 11.24% and distilled water 5.3%. The carbohydrate content in flour varies between 32.84% to 39.6%. This difference in composition is thought to be caused by variations in salinity and water chemical properties which affect the extraction of nutrients and fiber in seaweed. This research provides important insights in optimizing the Sargassum sp flour processing process. for food and feed industry applications, as well as the potential for maximum utilization of seaweed as an alternative nutritional source.